Endometrial patterns in abnormal uterine bleeding: a retrospective study - R., Sajeetha Kumari; M., Anuradha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Abnormal uterine bleeding (AUB) is a common reason for women of all ages to consult their gynecologist and is one of the most common debilitating menstrual problems ending up in hysterectomy in developing countries. The aim of the present study was to determine the clinical spectrum and frequency of pathologies in endometrial biopsy of patients with AUB in our population. We also tried to observe the incidence of various pathologies in different age groups presenting with abnormal uterine bleeding. Methods: The study was conducted in SRM Medical College Hospital and Research Centre, Tamil Nadu over a period of eight months. This was a retrospective study done on 217 patients presenting with abnormal uterine bleeding who underwent endometrial sampling in our hospital. The pattern of endometrial changes were studied and classified. Results: Age of the patients in our study ranged from 25 years to 68 years with maximum in the age group of 41-50 years. The commonest clinical feature was menorrhagia followed by metrorrhagia. Evaluation of the endometrium revealed various histopathological patterns like proliferative endometrium, secretory endometrium, disordered proliferative endometrium, pill endometrium, shedding endometrium, simple hyperplasia, complex hyperplasia, atrophic endometrium, endometrial polyp, carcinoma endometrium etc.The incidence of malignancy was 1.84%. Conclusions: Histopathological examination of the endometrium showed a wide spectrum of pathological changes ranging from normal endometrium to malignancy thus emphasizing the importance of endometrial sampling as an important diagnostic tool in the management of abnormal uterine bleeding. Accurate analysis of endometrial samplings is the key to effective therapy and optimal outcome.